Qualidade de Modelos Digitais de Elevação Utilizando Dados do SIGEF: Estudo de Caso para as Sub-Bacias do Ribeirão dos Mangues e Rio Soninho no Estado do Tocantins (Quality of digital elevation models using SIGEF data: Case study for the sub-basins of dos Mangues Stream and Soninho River in the state of Tocantins) - Pereira, Hugo Lopes; Catalunha, Márcio José; Borges Jr., Carlos Roberto; Sousa, Pablo Teixeira Gonzaga (Revista Brasileira de Geografia Física, 2019)
A utilização de Modelos Digitais de Elevação (MDE’s) aliados a técnicas de geoprocessamento são ferramentas de grande importância na modelagem hidrológica, no entanto sua utilização depende de estudos prévios que permitam detectar erros e imprecisões que geralmente estão associados a estes produtos. Estes estudos prévios consistem na comparação das altitudes dos Modelos digitais de Elevação em relação a altitudes de pontos de controle obtidas de fontes primárias (receptores GPS/GNSS geodésicos), verificação da existência de tendências, o Erro Médio Quadrático e a tolerância vertical das altitudes dos MDE’s. Nesse estudo foram utilizados dados de altimetria dos MDE’s SRTM 1 arc-segundo (Shuttle Radar Topography Mission), SRTM 3 arc-segundo, TOPODATA (Banco de dados geométricos do Brasil), ASTER GDEM (Advanced Spaceborne Thermal Emission and Reflection Radiometer), AW3D30 (Advanced Land Observation Satellite World 3D res. 30m) e ALOS PALSAR res. 12 m (Advanced Land Observation Satellite ) comparados com os dados altimétricos dos vértices dos polígonos dos imóveis certificados no SIGEF (Sistema de Gestão Fundiária) nas sub-bacias hidrográficas do ribeirão dos Mangues e rio Soninho, com objetivo avaliar o melhor MDE a ser usado em simulações hidrológicas nas referidas áreas. Os resultados mostram que o uso de pontos de referência oriundos do SIGEF para validação de MDE’s globais é uma alternativa viável em locais de vazio cartográfico, como é caso do estado do Tocantins. A B S T R A C T The use of Digital Elevation Models (DEMs) together with geoprocessing techniques are important tools in hydrological modeling, however their use depends on previous studies that allow detecting errors and inaccuracies that are usually associated with these products. These previous studies consist of comparing the elevations of the DEMs in relation to control point altitudes obtained from primary sources (GPS / GNSS geodetic receivers), verifying the existence of tendencies, the Mean Square Error and the vertical tolerance of the altitudes of the MDE's. In this study we used altimetry data from SRM 1 arc-second (Shuttle Radar Topography Mission), SRTM 3 arc-second, TOPODATA (Brazilian Geometric Database), ASTER GDEM (Advanced Spaceborne Thermal Emission and Reflection Radiometer), AW3D30 (Advanced Land Observation Satellite World 3D res 30m) and ALOS PALSAR res. 12 m (Advanced Land Observation Satellite) compared to the altimetric data of vertices of polygons of real estate certified in the SIGEF (Land Management System) in the River Basins dos Mangues Stream and Soninho River, with the objective of evaluating the best DEM to be used in hydrological simulations in these areas. The results show that the use of reference points from the SIGEF for validation of global DEMs is a viable alternative in locations of cartographic void, as is the case of the state of Tocantins.